6r+9=-(1-8r)

Simple and best practice solution for 6r+9=-(1-8r) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6r+9=-(1-8r) equation:



6r+9=-(1-8r)
We move all terms to the left:
6r+9-(-(1-8r))=0
We add all the numbers together, and all the variables
6r-(-(-8r+1))+9=0
We calculate terms in parentheses: -(-(-8r+1)), so:
-(-8r+1)
We get rid of parentheses
8r-1
Back to the equation:
-(8r-1)
We get rid of parentheses
6r-8r+1+9=0
We add all the numbers together, and all the variables
-2r+10=0
We move all terms containing r to the left, all other terms to the right
-2r=-10
r=-10/-2
r=+5

See similar equations:

| 5x-6x=17 | | 3a-3=5a-5 | | (x+5)/6=7 | | 400-(4*x^2)=0 | | 8/3=-2n | | 5n+10=5n-2 | | -3-(4+a)=-15 | | 17=14+19+b | | 2x−1=4 | | −4x+8−2x+5=31 | | 29x+87=4(3x+28) | | (5x+21)=(20x+34)=(12x-14) | | 6(-2-4n)=-3n+3(4-6n) | | 3x2-7=68 | | -2x-4-4x=8 | | 2x+26+3x=-33 | | -312=8+64p | | x-6+3=2(x-7) | | -12+9/11x=7 | | -8=6r+3-5 | | -84=-3(4+3m) | | 5/90=x/54 | | -7(x-8)+2=58 | | (8x-11)1/10=1 | | −4x−8−2x+5=31 | | F(0)=2^n | | 35x=31x+40 | | 2x-10+3=13 | | 7-7m=-13 | | −4−8−2x+5=31 | | 2^x=8^3+5x | | F(6)=10^n |

Equations solver categories